Pengaruh Multimedia Interaktif, Gaya Belajar dan Konsep Diri terhadap Prestasi Belajar Matematika - M. Ardiansyah (SAP (Susunan Artikel Pendidikan), 2021)
The purpose of this study is to find the effects of interactive multimedia, learning styles, and self-concept mathematics learning achievement using the three ways ANOVA. The research method used was a survey. The instruments were questionnaires and tests. The samples used were 90 respondents, 30 students each from SMP PGRI 32, SMP Ma?arif, and SMP Fatahilah Jakarta for the 2018/2019 school year using a purposive sampling technique. The results of the calculations showed that 1) interactive multimedia has a positive and significant effect on learning styles, 2) interactive multimedia has a positive and significant effect on self-concept, 3) learning style does not have  a significant effect on self-concept, 4) learning style has a positive and significant effect on learning achievement mathematics, 5) Self-concept has a positive and significant effect on mathematics learning achievement, 6) Interactive multimedia has an indirect effect on mathematics learning achievement through self-concept, 7) Interactive multimedia has an indirect and significant effect on mathematics learning achievement through learning styles, 8) Learning style does not have an indirect effect on mathematics learning achievement through self-concept, 9) Interactive multimedia does not have a positive and significant effect on self-concept through mathematics learning achievement.